The ZEPLIN-III dark matter detector: Performance study using an end-to-end simulation tool - Araújo, H. M. (2006)
We present results from a GEANT4-based Monte Carlo tool for end-to-end simulations of the ZEPLIN-III dark matter experiment. ZEPLIN-III is a two-phase detector which measures both the scintillation light and the ionisation charge generated in liquid xenon by interacting particles and radiation. The software models the instrument response to radioactive backgrounds and calibration sources, including the generation, ray-tracing and detection of the primary and secondary scintillations in liquid and gaseous xenon, and subsequent processing by data acquisition electronics. A flexible user interface allows easy modification of detector parameters at run time. Realistic datasets can be produced to help with data analysis, an example of which is the position reconstruction algorithm developed from simulated data. We present a range of simulation results confirming the original design sensitivity of a few times 10-8 pb to the WIMP-nucleon cross-section.